2018
DOI: 10.3390/molecules24010003
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Mechanisms of Echinatin and Licochalcone A

Abstract: Echinatin and its 1,1-dimethyl-2-propenyl derivative licochalcone A are two chalcones found in the Chinese herbal medicine Gancao. First, their antioxidant mechanisms were investigated using four sets of colorimetric measurements in this study. Three sets were performed in aqueous solution, namely Cu2+-reduction, Fe3+-reduction, and 2-phenyl-4,4,5,5-tetramethylimidazoline-1-oxyl 3-oxide radical (PTIO•)-scavenging measurements, while 1,1-diphenyl-2-picrylhydrazyl radical (DPPH•)-scavenging colorimetric measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 44 publications
2
41
0
Order By: Relevance
“…The experimental value of two hydrogen atoms (2.0124) had only 0.16% relative deviation from the calculated value (2.01565) [30], suggesting that there were two HAT reactions. On the basis of these experimental data and previous reports [62,63], a HAT reaction may firstly occur at the 4-OH of butein ( Figure 4A) [42,64]. Via the HAT reaction, butein is transformed to the butein-4-O-radical.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The experimental value of two hydrogen atoms (2.0124) had only 0.16% relative deviation from the calculated value (2.01565) [30], suggesting that there were two HAT reactions. On the basis of these experimental data and previous reports [62,63], a HAT reaction may firstly occur at the 4-OH of butein ( Figure 4A) [42,64]. Via the HAT reaction, butein is transformed to the butein-4-O-radical.…”
Section: Resultssupporting
confidence: 78%
“…Loss of the exocyclic double bond and loss of molecular planarity reduces the region of π-π conjugation. From resonance theory, saturation of the exocyclic α,β-double bond prevents stabilization of the free radical intermediate after the HAT reaction [62]. We previously demonstrated that these changes greatly decrease the antioxidant level [87,88].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the propagation stage, NAC‐3‐C • and DPPH • radicals were hypothesized to couple with each other to give the NAC‐DPPH adduct (I) via an RAF pathway. (I) may be further transformed into (II) via keto‐enol tautomerism to restore the aromaticity of the B‐ ring ,. Since neither (I) nor (II) is a free radical (Figure D), it is confirmed that the free radicals have been scavenged and the chain reaction is virtually terminated by the RAF reaction ,.…”
Section: Resultsmentioning
confidence: 90%
“…Our previous studies have revealed the following: (1) the DPPH • ‐scavenging reaction preferably proceeds via hydrogen atom abstraction, where one DPPH • radical accepts one hydrogen atom to form a DPPH−H molecule;, (2) in the chalcone antioxidant reaction, the 4‐OH group may donate a hydrogen atom prior to the other ‐OH's . On the basis of these two findings, the NAC molecule was hypothesized to transform into an NAC‐4‐O • intermediate radical via hydrogen atom abstraction (Figure A).…”
Section: Resultsmentioning
confidence: 99%